(untitled) (Research, Society and Development, 2023)
Vaccination coverage is an indicator that estimates the proportion of the vaccinated target population, and, in developing countries such as Brazil, this rate is below ideal in the quest to ensure good immunization coverage, and thus promote a reduction in injuries due to vaccine-preventable diseases. Ecological study of time series, retrospective and analytical using the DATASUS data base, which aimed to analyze the vaccination coverage and doses applied in children aged 0 to 1 year in all Brazilian regions, from 2012 to 2021. From 2014 onwards, there was a downward trend in the number of vaccine doses applied in Brazil, except in the southern region, which remained stationary. Regarding vaccination coverage, by region of Brazil, from 2012 to 2021, the North region showed a decrease throughout the period. The Northeast, South and Center-West regions found themselves decreasing between 2014-2021, and in the Southeast region there was a stationary trend in the same period. Further research is needed to assess the causes and seek solutions related to the drop in vaccination coverage and the number of doses applied in the regions of Brazil. Updating the vaccination schedule for children is of paramount importance in the quest to reduce the number of cases of vaccine-preventable diseases over the years, seeking to control and even eradicate various diseases in the future.